A hydrophobic release agent containing SiO2-CH3 submicron-sized particles for waterproofing mortar structures. (28th February 2019) - Izarra, Irene; Cubillo, Jose; Serrano, Angel; Rodriguez, Juan Francisco; Carmona, Manuel
Graphical abstract: Highlights: SiO2 -submicron-sized particles having CH3 groups were synthesized from MTES and TEOS. MTEOS were perfectly dispersed by sonication into the vegetable oil, except MTEOS-5. Non-agglomerated MTEOS were perfectly dispersed on the mortar surface. A release agent containing 3 wt% of MTEOS-2.5 allowed to achieve contact angles >145°. The compression strength of concrete specimens was not affected by the release agent. Abstract: Hydrophobic release agents were developed from SiO2 -CH3 submicron-sized particles containing hydrophilic and hydrophobic functional groups dispersed into a vegetable oil as support. The SiO2 -CH3 submicron-sized particles were synthesized by changing the molar ratio between the precursors Tetraethyl orthosilicate (TEOS) and Methyltriethoxysilane (MTES) from 0.66 to 5 (MTEOS-0.66 to MTEOS-5), being the relative amount of SiO2 -CH3 quantified by FTIR technique. Mortar specimens having hydrophobic properties were manufactured using 3 wt% of the above SiO2 -CH3 submicron-sized particles. Additionally, the concentration effect was studied by using MTEOS-0.66 within 3–10 wt%. The hydrophobic properties of the mortar specimens were checked by measuring the contact angle within water droplets and surface. The particle size increased with the MTES/TEOS molar ratio and according to the hydrophobic properties, the proper release agent must be synthesized by using MTEOS-2.5 dispersed into the vegetable oil and having a concentration of 3 wt%. This hydrophobic release agent led mortar surfaces with contact angles higher than 145°. Waterproofing and mechanical studies on concrete specimens allowed to conclude that this demoulding agent does not have a high penetration depth but improved the concrete waterproofing properties, without depletion in the compressive strength.